Demographic, Clinical, and Operative Factors Affecting Long-Term Revision Rates After Cervical Spine Arthrodesis. (21st September 2016) - Derman, Peter B.; Lampe, Lukas P.; Hughes, Alexander P.; Pan, Ting Jung; Kueper, Janina; Girardi, Federico P.; Albert, Todd J.; Lyman, Stephen
Abstract : Background: Limited data exist on long-term revision rates following cervical spine arthrodeses. The purposes of this study were to define reoperation rates after primary cervical arthrodeses and to identify risk factors for revisions. Methods: New York State's all-payer health-care database was queried to identify all primary subaxial cervical arthrodeses occurring in the 16 years from 1997 through 2012. A total of 87, 042 patients were included in the study cohort. Demographic information was extracted. Patients' preoperative medical comorbidities, surgical indications, and operative approaches were assembled using codes from the ICD-9-CM (International Classification of Diseases, Ninth Revision, Clinical Modification). The cohort was followed to revision surgical procedures, death, or the end of the study period. All subsequent contiguous spinal arthrodeses, including in the subaxial cervical spine, were considered revisions. The overall revision risk and the risk associated with various preoperative characteristics, surgical indications, and operative approaches were assessed using a Cox proportional hazard model. Results: During the study period, 6, 721 patients (7.7%) underwent revision. The median time to revision was 24.5 months. The probability of undergoing at least one revision by 192 months was 12.6%. Arthrodeses performed via anterior-only approaches had a significantly higher probability of revision (p < 0.001) at 13.4% (95% confidence interval [95% CI], 12.9% to 13.9%) than those performed via posterior approaches at 7.4% (95% CI, 6.6% to 8.4%) or circumferential (anterior and posterior) approaches at 5.2% (95% CI, 4.0% to 6.8%). This relationship persisted in multivariate analysis; compared with anterior surgical procedures, there was a significantly lower risk of revision (p < 0.001) for posterior surgical approaches at a hazard ratio of 0.76 (95% CI, 0.69 to 0.84) and circumferential approaches at a hazard ratio of 0.53 (95% CI, 0.42 to 0.66). Patient age of 18 to 34 years, white race, insurance status of Workers' Compensation or Medicare, and surgical procedures for spinal stenosis, spondylosis, deformity, and neoplasm were associated with elevated revision risk. Arthrodeses spanning few levels and those performed for fractures had a lower revision risk. Conclusions: Primary subaxial cervical spine arthrodeses had a probability of revision approaching 13% over a 16-year period, with elevated reoperation rates in patients undergoing anterior-only surgical procedures. Age, race, insurance status, surgical indication, and number of spinal levels included in the arthrodesis were also associated with reoperation risk. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.